EKSEKUSI OBJEK HAK TANGGUNGAN DALAM PENGEMBALIAN KREDIT (RECOVERY SECURED LOAN) PADA PT. BANK MANDIRI PERSERO, TBK CABANG MEDAN - HENNY HANDAYANI (PREMISE LAW JURNAL, 2017)
ABSTRACT The sale of collateral through auction in an attempt to return the credit of PT Bank Mandiri (Persero), Tbk. The implementation of auction through the court is considered as the right method in finding legal certainty in the process of auctioning collateral between the Bank and its clients. The result of the research showed that legal provisions which give the authority to the Bank execute the collateral through the process of auction were in accordance with Law No. 4/1996 on UUHT in which there is parate execution (in the name of God the Almighty) which has the same strength as Court’s Ruling. Legal remedy of the Bank to return the whole credit through the process of auction is by asking for the credit payment in the form of collateral and personal guarantee to debtors.